Taxonomic and nomenclatural notes on the genera Sarawakita Obenberger and Agrilus Curtis (Coleoptera: Buprestidae: Agrilinae) - Jendek, Eduard (Zootaxa, 2006)
The following taxonomic or nomenclatural changes are proposed: Sarawakita hewitti (Kerremans, 1912) comb. nov. (= latifrons Obenberger, 1924 syn. nov.); Agrilus subgenus Uragrilus Semenov, 1935 (= Epinagrilus Stepanov, 1954 unavailable name); Agrilus subgenus Robertius Théry, 1947 (type species A. robertii Chevrolat, 1838 by original designation, not A. taylori Théry, 1947) (= Arquagrilus Alexeev, 1998 syn. nov.); A. robertii correct original spelling. Lectotypes of Agrilus hewitti and Sarawakita latifrons are designated. The systematic position of the genus Sarawakita Obenberger, 1924 is discussed. An availability of Agrilus subgeneric names cited in works of Alexeev before 1998 are examined and discussed. The names of infrasubspecific entities proposed in Agrilus are examined for availability.